Influence of whitening dentifrices and mechanical brushing on color change and surface roughness of bulk fill resins - Mayara Zaghi Dal Picolo; Lúcia Trazzi Pietro; Josué Junior Araujo Pierote; Suelem Chasse Barreto; Carlos Tadeu dos Santos Dias; Luís Alexandre Maffei Sartini Paulilo (Universidade Estadual de Campinas, 2018)
Abstract: The use of whitening dentifrices during oral hygiene may cause surface modifications such as color change (ΔE) and increase surface roughness (Ra) of composite resin. Aim: This study aimed to evaluate the effect of whitening dentifrices and mechanical brushing on color change and surface roughness of Bulk Fill (Filtek Bulk Fill - F) and (Aura Bulk Fill - A) composite resins. Materials and methods: Sixty cylindrical specimens were fabricated of each composite resin. After initial color evaluations (Konica Minolta CM-700d), with D65 standard illuminant, and the surface roughness (Surfcorder SE 1700, Kosalab), the specimens were assigned (n=10) according to the whitening dentifrice used: True White (T), Colgate Total 12 Professional Whitening (D), Luminous White Advanced (L). Specimens were submitted to mechanical brushing (10,000 cycles); new color and surface roughness evaluations were taken. Data were analyzed by ANOVA, Duncan test and Dunnet test were used to identify differences between groups (α=5%). Results: The results showed that the tooth brushing time promoted a significant increase in ΔE of the FT group. The FD group exhibited intermediate values of ΔE and was similar to all groups tested. There was a significant increase in the surface roughness of the AD and AT groups after the mechanical tooth brushing. Conclusion: The results showed no significant changes were observed in surface roughness for F groups after toothbrushing. It be concluded that the color change and surface roughness of the composite resins after toothbrushing are dependent on the interaction between the composition of the composite resin and the characteristics of the dentifrice.